Intra- and Interspecies Conjugal Transfer of Plasmids in Gram-Negative Bacteria - Julia R. Savelieva; Daria A. Kondratieva; Maria V. Golikova (Biomedicines)
Background/Objectives: Plasmid-mediated resistance is a significant mechanism that contributes to the gradual decrease in the efficacy of antibiotics from various classes, including carbapenems. The aim of this study is to investigate the frequency of transfer of carbapenemase-encoding plasmids from K. pneumoniae to E. coli and P. aeruginosa. Methods: Matings were performed on agar with subsequent isolation of transconjugant, recipient, and donor colonies. The frequency of conjugation (CF) and minimum inhibitory concentrations (MICs) of meropenem were determined for the PCR-confirmed transconjugants. A pharmacodynamic study was conducted using a hollow-fiber infection model on E. coli transconjugant in order to evaluate its viability in the presence of therapeutic concentrations of meropenem. Results: CF for K. pneumoniae-K. pneumoniae was similar to that for K. pneumoniae-E. coli and was higher the higher was meropenem MIC of the K. pneumoniae donor. The meropenem MICs for K. pneumoniae and E. coli transconjugants were higher (0.25–4 μg/mL) compared to recipients (0.03–0.06 μg/mL). P. aeruginosa did not acquire plasmids from K. pneumoniae. In pharmacodynamic experiments, an E. coli transconjugant with MIC of 2 mg/L within the “susceptibility range”, failed to respond to meropenem treatment. Conclusions: The frequency of conjugation between K. pneumoniae and E. coli falls within a similar range. A higher permissiveness of K. pneumoniae for plasmids from K. pneumoniae, i.e., within the same species, was observed. Conjugation did not occur between K. pneumoniae and P. aeruginosa. The transconjugants with meropenem MICs with borderline susceptibility may pose a potential threat to the efficacy of meropenem.